Implementation of QR code for School's Cooperative System / Nor Idatasya Junus - Junus, Nor Idatasya (2017)
School's Cooperative System, named as e-COOP, is a system for the school's cooperative staffs that can be used at schools for a better cooperative management, which using the QR code technology for the student identification. This system will be able to help the cooperative staffs to manage the cooperative and the processes of buy and pay in more efficient way. The e-COOP process was organize and guide by using four phases methodology, known as System Development Life Cycle (SDLC), starting with planning and analyzing the system requirement and suitable technique for the e-COOP to design the interface of the system, develop a web-based system using the QR code technology, and evaluate the functionalities of the e-COOP that is implemented for the school. The e-COOP use the technology of QR Code, which is suitable to be implemented in the system as a unique student identification. From the cooperative staffs' evaluation, as the user of the system, they found that this system is really useful for the cooperative management because computerized system is considered to be a good choice for the school as paper less. All the functionalities in the e-COOP system are tested to ensure that the fictions are working and well-functioned. The QR codes are successfully generated from the student IC and the QR code tagging and reading are well-functioned for the student identification. The user will be notified with the proper message for the wrong user input. This system currently use a localhost as the server which is limited for other users' access. There are some limitation that can be improved especially for the future such as the system can be done as a centralized web-based system which is more efficient and also on the part of security can be improved. In addition, the system can be improved for the cooperative payment management as this system project is only focusing on buying and displaying record of buyers.